2008
DOI: 10.3758/mc.36.2.282
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and position information in working memory for visual textures

Abstract: 282Working within a framework of exemplar-similarity models of memory (see, e.g., Estes, 1994;Kahana & Sekuler, 2002;Kahana, Zhou, Geller, & Sekuler, 2007;Medin & Schaffer, 1978;Nosofsky, 1986;Nosofsky & Kantner, 2006), we used sinusoidal luminance gratings as stimuli in a modified Sternberg (1966) recognition task. The metric properties of the grating stimuli were exploited to test a novel prediction generated by combining the exemplar-similarity approach with an explicit, signal detection account of decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…This suggests that the variance in items’ features is also an important determinant of recognition responses. Furthermore, it has been shown that subjects’ memory for serial position of individual study items is more accurate when when homogeneity of the study items is lower (Yotsumoto et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the variance in items’ features is also an important determinant of recognition responses. Furthermore, it has been shown that subjects’ memory for serial position of individual study items is more accurate when when homogeneity of the study items is lower (Yotsumoto et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Our results showed the same patterns of the similarity effect for lure intervals as for lure textures, and thus confirmed that the item representations of time intervals were similar to those of visual textures. The similarity effect for visual items has been well investigated in previous studies (e.g., Kahana and Sekuler, 2002 ; Zhou et al, 2004 ; Yotsumoto et al, 2008 ), but that for temporal items was examined for the first time in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…Stimuli for each trial were drawn from a pool of two-dimensional (2D) sinusoidal gratings that are often employed in studying recognition/working memory (e.g., Kahana and Sekuler, 2002 ; Yotsumoto et al, 2008 ). Gratings were of 25 different spatial frequencies, derived by combining five vertical and five horizontal frequencies of 1.51, 1.75, 2, 2.25, and 2.49 cycles per degree (CPD), similar to those used by Yotsumoto et al (2008) . The gratings were presented at 10 different time intervals from 0.25 to 0.97 s, with a linear increment of 0.08 s. The numbers of different visual or temporal stimuli rendered the probe prediction impossible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Episodic memory operates via encoding and retrieval processes, and can be measured using recognition tasks (Diana, Yonelinas, & Ranganath, 2007; Haist, Shimamura, & Squire, 1992; Yotsumoto, McLaughlin, Kahana, & Sekuler, 2008). Recognition is the ability to determine if a currently presented item had been encountered previously (Yonelinas, 2002).…”
Section: Introductionmentioning
confidence: 99%